IMPLEMENTASI PROGRAM BIMBINGAN BIMBINGAN DAN KONSELING DI SMP NEGERI 1 PEKANBARU TAHUN 2017 - Feti Bimariya Suwita; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract:The implementation of Guidance and Counseling program is a very important program in an educational institution. But in reality, in the implementation of the program there are usually obstracles such as lack of time allocation for BK and facilities and infrastructure that are inadequate for the implementation of the program. The purpose of this research is to find out what kind of type and content of the program BK and how the implementation of the program BK at SMP Negeri 1 Pekanbaru in 2017. This research uses descriptive qualitative research method to describe how implementation of program BK in SMP Negeri 1 Pekanbaru. Subject in this research is one BK teacher. From the results of research indicate that the type of program BK in SMP Negeri 1 Pekanbaru is a monthly program, semester program and annual program. The content of the program are in the form of ten types of services applied to the four areas of guidance namely personal guidance, social counseling, tutoring learning and career guidance counseling. The implementation of program BK in SMP Negeri 1 Pekanbaru has been implemented in accordance with the problems faced by student, but there are still some programs that have not been done well because of obstacles in the implementation. So, basically the implementation of the program in SMP Negeri 1 Pekanbaru already implemented, but still not maximal because there is still a barrier that is the lack of time allocation and facilities and infrastructure are not adequate.Key Word: Guidance and Counseling Program, Implementation